Potential pharmacological mechanisms of tanshinone IIA in the treatment of human neuroblastoma based on network pharmacological and molecular docking Technology - Tang, Ning; Wang, Yan; Miao, Jiarui; Zhao, Yang; Cao, Yue; Sun, Wentao; Zhang, Jingke; Sui, Hua; Li, Bing (Frontiers in Pharmacology, 2024)
Tanshinone IIA (Tan-IIA) is the main bioactive component of Chinese herbal medicine salvia miltiorrhiza (Danshen). Sodium sulfonate of Tan-IIA is widely used in the treatment of cardiovascular and cerebrovascular diseases. Tan-IIA also has inhibitory effects on tumor cells such as gastric cancer, but its therapeutic effect and mechanism on human neuroblastoma have not been evaluated, so its pharmacological mechanism is systematically evaluated by the combined method of network pharmacology and molecular docking. PharmMapper and SwissTargetPrediction predicted 331 potential Tan-IIA-related targets, and 1152 potential neuroblastoma-related targets were obtained from GeneCards, DisGeNET, DrugBank, OMIM and Therapeutic Target databases (TTD), 107 common targets for Tan-IIA and neuroblastoma. Through gene ontology (GO) functional annotation, Kyoto Encyclopedia of Genes and Genomesa (KEGG) pathway enrichment, protein-protein interaction (PPI) network and cytoHubba plug-in, 10 related signal pathways (Pathways in cancer, PI3K-Akt signaling pathway, Prostate cancer, etc.) and 10 hub genes were identified. The results of molecular docking showed that Tan-IIA could interact with 10 targets: GRB2, SRC, EGFR, PTPN1, ESR1, IGF1, MAPK1, PIK3R1, AKT1 and IGF1R. This study analyzed the related pathways and targets of Tan-IIA in the treatment of human neuroblastoma, as well as the potential anticancer and anti-tumor targets and related signaling pathways of Tan-IIA, which provides a reference for us to find and explore effective drugs for the treatment of human neuroblastoma.